Proteomic Identification of an Endogenous Synaptic SUMOylome in the Developing Rat Brain - Pronot, Marie; Kieffer, Félicie; Gay, Anne-Sophie; Debayle, Delphine; Forquet, Raphaël; Poupon, Gwénola; Schorova, Lenka; Martin, Stéphane; Gwizdek, Carole (Frontiers in Molecular Neuroscience, 2021)
Synapses are highly specialized structures that interconnect neurons to form functional networks dedicated to neuronal communication. During brain development, synapses undergo activity-dependent rearrangements leading to both structural and functional changes. Many molecular processes are involved in this regulation, including post-translational modifications by the Small Ubiquitin-like MOdifier SUMO. To get a wider view of the panel of endogenous synaptic SUMO-modified proteins in the mammalian brain, we combined subcellular fractionation of rat brains at the post-natal day 14 with denaturing immunoprecipitation using SUMO2/3 antibodies and tandem mass spectrometry analysis. Our screening identified 803 candidate SUMO2/3 targets, which represents about 18% of the synaptic proteome. Our dataset includes neurotransmitter receptors, transporters, adhesion molecules, scaffolding proteins as well as vesicular trafficking and cytoskeleton-associated proteins, defining SUMO2/3 as a central regulator of the synaptic organization and function.